Pengaruh Ukuran Perusahaan dan Leverage Terhadap Integritas Laporan Keuangan pada Perusahaan Sektor Infrastruktur, Utilitas dan Transportasi yang Terdaftar di Bursa Efek Indonesia Periode 2017-2019 - Ni Ketut Ayu Ashari (UNHI Press, 2022)
The purpose of this research is to determine the impact of firm size and leverage on the integrity of financial statements. The population in this study was all companies on the IDX in the infrastructure, utility, and transportation sectors, and the sampling technique used was purposive sampling, yielding a sample of 69. Multiple linear regression was used as a data analysis technique. According to the findings of this study, the firm size variable has no significant effect on the integrity of financial statements in infrastructure, utility, and transportation sector companies listed on the Indonesian stock exchange. While the leverage variable has a positive and significant effect on the integrity of financial statements in the infrastructure, utilities, and transportation sectors listed on the Indonesian stock exchange.